Pengaruh Model Pembelajaran Kooperatif Tipe Artikulasi yang Disertai LKS terhadap Hasil Belajar Siswa Biologi Kelas XI MIA SMA Negeri 1 Kota Solok - Yola Gustia Sari; Afrahamiryano Afrahamiryano; Darmanella Dian Eka Wati (Eduscience Development Journal, 2020)
The low learning outcomes Biology of second grade MIA SMA Negeri 1 Kota Solok requires teachers to look for alternatives to increase student learning outcomes by creating a warm learning atmosphere between students and teachers so that good communication. One of- the ways that can be used is the Cooperative Learning Model Articulation with Student Worksheet (LKS). The problem of this research is "Is there a learning effect of Cooperative Learning Model Articulation with LKS on learning outcomes Biology second grade of MIA SMA Negeri 1 Solok?". This study aims to determine the is there a learning effect of Cooperative Learning Model Articulation with LKS on learning outcomes Biology second grade of SMA Negeri 1 Kota Solok. The hypothesis of this study is the influence of the use of Cooperative Learning Model Articulation with LKS on student learning outcomes Biology class XI MIA SMA Negeri 1 Solok. This research is experimental. The Population in this research is in the second grade of MIA SMA Negeri 1 Kota Solok registered in 2015/2016 totalling 244 people. The technique sampling was conducted as random sampling. Samples selected as the experimental class is the second grade of MIA 4 with several students 36 people using Cooperative Learning Model Articulation with LKS, and the control class is the second grade of MIA 5 with some students are 36 people using Cooperative Learning Model Articulation without LKS. Based on the results of hypothesis testing using the z test obtained, z calculate = 1,93 and z table = 1,78, so z calculate > z table at a confidence level of 95%, which means that H0 rejected and H1 accepted. the biology student learning outcomes using Cooperative Learning Model Articulation with LKS are better than Cooperative Learning Model Articulation without LKS.